Capital markets, derivatives, and the law : evolution after crisis - Rechtschaffen, Alan N. (Oxford : New York : Oxford university press, 2014)
This edition serves as an essential guide to better understand the legal and business considerations of capital market participation. It investigates the impact of the financial crisis on capital markets and regulation and provides the reader with the tools to recognize vulnerabilities in capital market trading activities.
Foreword by Jean-Claude Trichet
Includes bibliographical references and index.
nmn 05/12/17
Loans
Keywords: Financial instruments; Derivative securities; Capital market; Securities industry; Global Financial Crisis, 2008-2009.; United States